1988
DOI: 10.1029/gl015i006p00621
|View full text |Cite
|
Sign up to set email alerts
|

The depth of seismic faulting and the upper transition from stable to unstable slip regimes

Abstract: Abstract. A number of observations indicate that an upper stability transition occurs along well-developed faults, such as the San Andreas, as a result of unconsolidated gouge within shallow regions of these faults. These observations include the depth distribution of seismicity along faults with and without well-developed gouge zones, correlations between seismicity and shallow crustal structure, and modeling of coseismic and post-seismic slip. In addition, recent experimental friction studies indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
281
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(294 citation statements)
references
References 20 publications
12
281
1
Order By: Relevance
“…Studies of interplate seismicity have shown that large earthquakes generally initiate within specific depth limits, generally between ~10 and 40 km (Byrne et al, 1988;Pacheco et al, 1993;Tichelaar and Ruff, 1993;Scholz, 2002), but the precise limits vary with temperature (Hyndman et al, 1997). This observation led to a conceptual model in which the subduction thrust is divided into three zones (e.g., Scholz, 1988). In the shallowest zone, plate convergence is accommodated by stable (aseismic) slip.…”
Section: Background Seismogenesis At Convergent Marginsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of interplate seismicity have shown that large earthquakes generally initiate within specific depth limits, generally between ~10 and 40 km (Byrne et al, 1988;Pacheco et al, 1993;Tichelaar and Ruff, 1993;Scholz, 2002), but the precise limits vary with temperature (Hyndman et al, 1997). This observation led to a conceptual model in which the subduction thrust is divided into three zones (e.g., Scholz, 1988). In the shallowest zone, plate convergence is accommodated by stable (aseismic) slip.…”
Section: Background Seismogenesis At Convergent Marginsmentioning
confidence: 99%
“…Pore pressures in excess of hydrostatic pressures decrease the effective normal stress, thereby limiting the shear stress, and, coupled with the low consolidation and lithification state of sediment in the updip aseismic portion of the fault, may explain the lack of seismicity. A downdip decrease in pore fluid pressure increases the normal stress, leading to greater instability in plate sliding (Scholz, 1988). …”
Section: Expedition 344 Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Its relation with stress drop has been experimentally simulated with granular flow models [e.g., Higashi and Sumita, 2009]. Similar factors can play a role in subduction thrusts, favored by dehydration reactions in the subducting lithosphere [e.g., Pytte and Reynolds, 1988], changes in lithification state [Marone and Scholz, 1988;Marone and Saffer, 2007] and diagenetic processes [Moore and Saffer, 2001]. Thus, the initially rough profile of the lithosphere at the trench will be gradually smoothed as subduction evolves, minimizing roughness fluctuations with depth [Wang, 2010a].…”
Section: Implications For Subduction Zone Seismogenesismentioning
confidence: 99%